Be careful what you wish for: CEO and analyst firm performance attributions and CEO dismissal - Park, Sun Hyun; Chung, Sung Hun (Brian); Rajagopalan, Nandini (Strategic Management Journal, 2021)
Abstract Research Summary Chief executive officers (CEOs) often make internal attributions of positive firm performance outcomes by highlighting their strategic choices as the cause of favorable performance results. We investigate the dynamic consequences of CEO internal performance attributions along a CEO's tenure. CEO internal attributions create an expectation that favorable firm performance will continue under the CEO's leadership. When firm performance turns negative, however, financial analysts also make internal attributions, pointing to the strategies highlighted by the CEO as the cause of performance downfall. Analysts' internal attributions provide a board with a legitimate account casting doubt on the CEO's leadership efficacy, increasing the likelihood of dismissal. We find strong empirical support for our hypotheses in a panel dataset that tracks CEO and analyst interviews in news media around quarterly earnings announcements. Managerial Summary While prior studies of chief executive officers (CEOs) dismissal have considered different factors leading to CEO dismissal, our study highlights the role played by the CEO's own public performance attributions. Our results show that when CEOs attribute positive performance outcome to their leadership, financial analysts are also more likely to attribute subsequent negative performance outcomes to their leadership, which in turn ultimately leads to CEO dismissal. Given the difficulty of predicting firm performance over an extended period of time, CEOs should be aware that when they take credit for positive performance outcomes they may be setting themselves up for subsequent blame from external constituents seeking explanations for negative performance outcomes. Thus, our results suggest that CEOs may stand to gain from more self‐effacing behaviors.